Family, work, economy, or social policy: Examining poverty among children of single mothers in affluent democracies between 1985-2016 - Amie Bostic (Luxembourg Income Study (LIS), 2023)
Children of single mothers face higher rates of poverty than children in two-parent households in practically every affluent democracy. While this difference is widely acknowledged, there is little consensus regarding the causes of their poverty and, as a result, little consensus on the best way to address poverty among these children. Explanations include both individual-level, structural, and political explanations in four areas: family structure, labor force activity, economic performance, and welfare generosity. Previous research, however, tends to focus on only one of these four aspects at a time. Using data from the Luxembourg Income Study and the Organisation for Economic Co-operation and Development, spanning a period of 31 years and 25 countries, I test each of these four explanations, examining the effects on children in single mother households separately (n=105,814) and children in both single mother households and children in two-parent households (n=668,549), conducting random intercept between-within logistic regression analysis. Individual-level measures of family structure and labor market activity affect child poverty generally in the expected way. Taking advantage of the longitudinal data at the country level, I focus on within-country change of the structural and political variables. Within-country economic performance is not significantly related to poverty, but welfare generosity, namely family allowances, significantly reduce the odds of poverty. Further, while the effects of family allowance spending are similar for children in both single mother and two parent households, they are stronger for the former than the latter. Yet, the disadvantage of living in a single mother household persists.
Keywords: 330; poverty; child poverty; single mothers; social policy; family allowances